The influence of school climate on high school teachers’ job satisfaction in a conflict-affected country - Abdul Qawi Noori; Hamdan Said; Sayeed Naqibullah Orfan; Siti Nisrin Mohd Anis (Institute of Advanced Engineering and Science, 2024)
School climate plays a vital role in a teacher’s job performance, satisfaction, and school effectiveness. There were abundant studies on school climate and effectiveness and its relationship with teachers’ job performance and job satisfaction for primary and secondary schools in developed and developing countries. Unfortunately, there were scarce studies on teachers’ satisfaction in underdeveloped countries with prolonged conflicts and government instability. This study investigated the influence of school climate on teachers’ job satisfaction in a conflict-affected country, Afghanistan. It employed a survey questionnaire to collect data from public high school teachers in the Takhar province of Afghanistan. The data were descriptively and inferentially analyzed with the aid of statistical package for the social sciences (SPSS). Despite prolonged conflicts and government instability, the study found a statistically positive correlation between school climate and high school teachers’ job satisfaction. It also revealed statistically significant differences in the satisfaction level of teachers by their demographic variables, i.e., gender, educational qualification, age, and working experience. The study suggests that education administrators, school leaders, and other stakeholders develop a policy advancing a peaceful and conducive learning environment to improve student’s learning outcomes, teachers’ job performance and satisfaction, and school effectiveness. Future studies may qualitatively examine schools in different parts of the country.